Upaya Pembelajaran Kitab Fathu Al-Qarib Dalam Mempertahankan Warisan Keilmuan Islam Di Kelas VIII SMP Nur Lintang Pondok Pesantren Karang Santri Bandunggede Kedu Temanggung - Channa Nafisah; Ngarifin Shidiq; Mukromin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research was conducted in response to the following issues: the students’ low understanding of Fathu al-Qarib; the declining interest learning, causing it to fade from Islamic education; inadequate enthusiasm; a lack of innovative and contextual teaching methods; and challenges posed by globalization and modernization. In light of these problems, this study aims to: 1) explore the concept of teaching; 2) examine how its learning is implemented; and 3) identify the supporting and inhibiting factors in efforts to teach. A qualitative field research methodology was employed. The findings indicate that the learning method applied at Karang Santri Islamic boarding school is the sorogan method. Additionally, the school has incorporated musyāwarah (group discussion) into their teaching of the Fathu al-Qarib book. The inhibiting factors include students’ lack of concentration during learning sessions and the absence of sanctions for those who do not attend. On the other hand, the boarding school environment serves